A bourdieuian analysis of foundation programmes within the field of engineering education : two South African case studies - Kloot, Bruce (Department of Chemical Engineering, 2014)
While analyses of foundation programmes have traditionally focused on pedagogical innovations, curriculum design or student experience, this thesis investigates social structures in order to examine the potential that foundation programmes, in general, hold for the transformation of higher education in South Africa.